Унійна польськомовна проза волинських культурних осередків XVII ст. - Сухарєва, Світлана; Sukharieva, Svitlana (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті охарактеризовано унійну польськомовну прозу, створену на Волині в XVII ст. Особливу увагу звернено на діяльність Іпатія Потія, Касіяна Саковича та Мелетія Смотрицького у другий, унійний період його творчості. Серед культурних осередків волинського регіону виділено Володимир-Волинський, Острог, Луцьк і Дермань./ Union Polish prose, created in Volyn in XVII century is characterized in the article. The main attention is payed to works of Ipatii Potii, Kasiyan Sakowych and Meletii Smotryckii in the second period of his works. It’s marked the role of Kyrylo Terleckii in signing of the Brest Union. Among cultural centres Volodymyr-Volynski, Ostrog, Lutsk and Derman are marked out. Polemical Polish discourse is represented complex, taking into account thesis character and apologetic direction. The main dominant of Polish-fiction of XVII century in Volyn as well as its types are defined on the basis of the analyzed material. It is concluded that the Volyn period of polemists creativity was a significant contribution to the development of Polish polemical treatises and epistolary heritage.
Union Polish Prose of Volynian Cultural Centres of XVII Century
Сухарєва С. Унійна польськомовна проза волинських культурних осередків XVII ст. / Світлана Сухарєва // Науковий вісник Східноєвропейського національного університету. Сер. «Філологічні науки. Літературознавство». – 2014. – № 9 (286). – С. 137-141.
Keywords: риторика; апологетика; полемічний дискурс; волинські культурні осередки; книгодрукування; rhetoric; polemical discourse; apologetics; Volynian cultural centres; book-printing